AKIBAT HUKUM PENGUNDUHAN KARYA CIPTA FOTOGRAFI DALAM MEDIA SOSIAL INSTAGRAM DAN PERLINDUNGANNYA - Shabilla Nur Aisyah (Fakultas Hukum Universitas Stikubank, 2020)
Photography copyright works in Istagram are regulated in Article 40 paragraph (1) letter k of Law number 28 of 2014 concerning Copyright. The background of this research is that the public does not understand the element of copyright protection in every photographic work uploaded on Instagram social media. When someone downloads a photographic work without the permission of the owner of the work, even though this has often been done, from a legal standpoint there will be legal consequences and even lead to sanctions. The problem is whether the state provides protection for photographic copyrighted works and what are the legal consequences if the download is done without permission. The method used in this research is normative juridical, namely research based on secondary data, which is then analyzed qualitatively and presented in a qualitative form.The results show that the state has protected photographic copyright works, through Article 1365 jo 1367 KIHPer, Article 25 of Law No. 19 of 2016 concerning Electronic Information and Transactions, Article 40 paragraph (1) letter k and Article 59 of Law No. 28 of 2014 concerning Copyright and Joint Regulations of the Minister of Law and Human Rights and the Minister of Communication and Information Technology No. 14 of 2015 and No. 26 of 2015. The legal consequence is that if a person makes a download without permission, under Article 113 of the Copyright Law, he can be sentenced to a maximum of 4 years in prison and / or a maximum fine of 1 Billion, based on Article 48 of the ITE Law, imprisonment of 8 - 9 years and / or 2 M. Keywords: Legal Protection, Copyright, Photography, Social Media